The resilience and sensitivity of Northeast Atlantic deep water [epsilon]Nd to overprinting by detrital fluxes over the past 30,000 years - Blaser, Patrick; Pöppelmeier, Frerk; Lippold, Jörg; Link, Jasmin; Hoffmann, Julia; Frank, Norbert (Geochimica et cosmochimica acta, 2019)
The neodymium isotope proxy has become a valuable tool for the reconstruction of past ocean water mass provenance and mixing. For its accurate application, knowledge about the origin and preservation of Nd in sedimentary archives is crucial. Recently, concerns have emerged regarding the applicability of neodymium isotopes as a conservative palaeo water mass tracer, given potential Nd fluxes from sediments into bottom waters (Abbott et al., 2015a) and inferred relabelling of ocean waters by settling detrital material (Roberts and Piotrowski, 2015). Consequently, a decoupling of water mass provenance and proxy variations may arise. We investigate the mobility of Nd around extreme detrital sedimentation events such as glacial ice rafting pulses and turbidite deposition in the Northeast Atlantic. The constructed records from sediment leachates span extreme Nd isotope variations including volcanic (εNd∼0) and Laurentian (εNd∼−27) sources. We find that Nd was released into pore waters from reactive detritus inside some detrital layers during early diagenesis, thereby overprinting any archived bottom water Nd signature and precluding the reconstruction of past water mass provenance during the affected time intervals. However, we do not observe any definite indication of diffusive vertical migration of Nd into adjacent layers. Furthermore, bottom water Nd isotope signatures were not modified to a measurable degree by any potential benthic flux of Nd during the deposition of these detrital sediment layers. Consequently, the Nd isotope composition of the pelagic glacial Northeast Atlantic water masses were resilient to such episodic large detrital fluxes. Apart from extreme local sedimentation events, we confirm the presence of detritally overprinted deep waters north of 47°N during the peak glacial from comparison of Northeast Atlantic depth transects. We furthermore suggest that the sensitivity of deep waters to this overprinting effect increased during periods of reduced Atlantic Meridional Overturning Circulation and elevated ice rafting. Overall, our study demonstrates that a thorough evaluation of the proportion of Nd originating from physical water mass advection versus in situ chemical inputs is crucial for the reliable application of Nd isotopes as a water mass tracer.
available online 24 October 2018
Gesehen am 09.05.2019